2020
DOI: 10.3389/fpsyg.2020.00218
|View full text |Cite
|
Sign up to set email alerts
|

I Can See Clearly Now: Episodic Future Thinking and Imaginability in Perceptions of Climate-Related Risk Events

Abstract: Climate change is statistical, abstract and difficult to comprehend directly. Imagining a specific, personal episode where you experience consequences of climate change in the future (episodic future thinking) may bring climate change closer, thus increasing the perceived risk of climate-related risk events. We conducted an experiment to test whether episodic future thinking increased the perceived risk of climate-related risk events and climate change in general, as compared to thinking about the future in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Past studies have shown that episodic simulation can support decision making in other domains, improving both patience (44,75) and prosociality (46). However, other studies have shown no effect of episodic simulation on risk perception (76,77), perhaps because narratives are more powerful when they are paired with statistics (57). Importantly, our intervention is the first to combine an episodic simulation with prediction error.…”
Section: Discussionmentioning
confidence: 86%
“…Past studies have shown that episodic simulation can support decision making in other domains, improving both patience (44,75) and prosociality (46). However, other studies have shown no effect of episodic simulation on risk perception (76,77), perhaps because narratives are more powerful when they are paired with statistics (57). Importantly, our intervention is the first to combine an episodic simulation with prediction error.…”
Section: Discussionmentioning
confidence: 86%
“…Past studies have shown that episodic simulation can support decision making in other domains, improving both patience ( 43 , 76 ) and prosociality ( 46 ). However, other studies have shown no effect of episodic simulation on risk perception ( 77 , 78 ), perhaps because narratives are more powerful when they are paired with statistics ( 57 ). Importantly, our intervention combines an episodic simulation with prediction error.…”
Section: Discussionmentioning
confidence: 95%
“…By showing that EFT is particularly effective in nudging individuals characterized by choice impulsivity, we corroborate that it may be a helpful mechanism for optimizing future-oriented decisions. We further envision that EFT may have a similar impact in other domains that inherently entail a tradeoff with the future, including societal challenges such as promoting more sustainable behavior (Bø & Wolff, 2020;Lee et al, 2020;Williams & Benoit, 2021). Peters & Büchel, 2010 and our subsequent publication (Benoit et al, 2011), we were excited to witness the accumulation of research into the impact of EFT on intertemporal choice.…”
Section: Caveatsmentioning
confidence: 99%